2019
DOI: 10.1111/ssqu.12603
|View full text |Cite
|
Sign up to set email alerts
|

How Governance and Disasters Shape Renewable Energy Transitions: The Case of Japanese Mega‐Solar*

Abstract: Objectives This mixed‐methods study examines whether governance and disasters affect towns that host more renewable power plants, focusing on solar facilities in Japan after the 3/11 disaster. Methods I tested the effects of various factors on multiple sizes of feed‐in tariff certified solar power plants with negative binomial models. I confirmed those effects through process tracing using 14 interviews with local stakeholders from two prefectural case studies. Results Most prefectures boost solar power plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Third, we use matched samples in two countries to clarify two conflicting findings in past literature. Past scholars found that disaster damage was linked to increased adoption of solar farms in Japanese communities (Mochizuki and Chang 2017), but later studies found the opposite (Fraser 2019). We find that among similar communities, differing only in their exposure to disaster, they do tend to adopt more solar after crisis, consistent with Mochizuki and Chang's findings.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Third, we use matched samples in two countries to clarify two conflicting findings in past literature. Past scholars found that disaster damage was linked to increased adoption of solar farms in Japanese communities (Mochizuki and Chang 2017), but later studies found the opposite (Fraser 2019). We find that among similar communities, differing only in their exposure to disaster, they do tend to adopt more solar after crisis, consistent with Mochizuki and Chang's findings.…”
supporting
confidence: 85%
“…While policies of other types may diffuse from state to state, Matisoff (2008) found that the internal traits of governments mattered more to solar policy than diffusion, through motivations, resources, and obstacles specific to those governments. While national-level dynamics do not explain variation from city to city, recent studies have reapplied Matisoff's perspective to the city level, finding that governments' motivations, resources, and obstacles still matter to solar adoption (Fraser 2019).…”
Section: Solar Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some found that some towns which suffered more damage in the 3.11 disaster hosted more mega-solar in the years following (Mochizuki & Chang, 2017), barriers to obtaining insurance, finding absentee land owners, and rezoning for solar meant that overall, disaster struck towns tend not to host solar. Instead Prefectural intervention thus significantly improves their ability to participate in renewable energy transition (Fraser, 2019b). Overall, prefectures seek work to meet prefectural targets for renewables while financially or logistically supporting ventures such as hydrogen power stations and small scale public microgrids, which are not currently in demand but represent important investments in technology adoption.…”
Section: Prefectures and Regional Economicsmentioning
confidence: 99%
“…This remained true with a representative sample, even after incorporating the changing electricity prices, local jobs, fixed assets tax revenue for municipalities, reductions in air pollution and CO 2 emissions, and community preferences on energy policy (Chapman & Fraser, 2018; Fraser & Chapman, 2020). Even so, representatives from the Agency for Natural Resources and Energy report intentions to focus financial support in the future on small, community projects instead of the corporate beneficiaries of 2012 current FiT (Fraser, 2019b).…”
Section: Changing Roles In Renewable Powermentioning
confidence: 99%